2018
DOI: 10.1002/ece3.3902
|View full text |Cite
|
Sign up to set email alerts
|

Direct effects of warming increase woody plant abundance in a subarctic wetland

Abstract: Both the direct effects of warming on a species’ vital rates and indirect effects of warming caused by interactions with neighboring species can influence plant populations. Furthermore, herbivory mediates the effects of warming on plant community composition in many systems. Thus, determining the importance of direct and indirect effects of warming, while considering the role of herbivory, can help predict long‐term plant community dynamics. We conducted a field experiment in the coastal wetlands of western A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The increased dominance of shrubs in this coastal wetland~AD 1950 follows an increase in GDD 0 at AD 1931 (Figure 2b). Northward expansion of shrub communities and increased productivity in response to recent warming has been widely documented across the tundra (Elmendorf et al, 2012;Myers-Smith et al, 2011;Tape et al, 2006) and directly linked to increased shrub and decreased sedge abundance in an Alaskan coastal wetland (Carlson et al, 2018). Isostatic uplift can lead to a drop in relative sea level and lowering of the water table, increasing dryness to facilitate sedge to shrub succession (Klinger & Short, 1996).…”
Section: Potential Impact Of Herbivory On Arctic Coastal Wetlandsmentioning
confidence: 99%
“…The increased dominance of shrubs in this coastal wetland~AD 1950 follows an increase in GDD 0 at AD 1931 (Figure 2b). Northward expansion of shrub communities and increased productivity in response to recent warming has been widely documented across the tundra (Elmendorf et al, 2012;Myers-Smith et al, 2011;Tape et al, 2006) and directly linked to increased shrub and decreased sedge abundance in an Alaskan coastal wetland (Carlson et al, 2018). Isostatic uplift can lead to a drop in relative sea level and lowering of the water table, increasing dryness to facilitate sedge to shrub succession (Klinger & Short, 1996).…”
Section: Potential Impact Of Herbivory On Arctic Coastal Wetlandsmentioning
confidence: 99%
“…Plant communities are already responding to these temperature changes. Preferred summer forages like deciduous shrubs and graminoids (White et al 1975, Thompson and McCourt 1981, Denryter et al 2017) are thriving at the expense of less palatable evergreen shrubs and nonvascular plants as warming continues across much of the Arctic (Sturm et al 2001, Wahren et al 2005, Tape et al 2006, 2012, Hobbie et al 2017, Carlson et al 2018). While the acceleration of green‐up has become a foundation for understanding warming's direct impact on forage during the spring and summer (Prevéy et al 2017, 2019, Bjorkman et al 2018), the consequences of changes to winter weather and its subsequent effect on forage phenology, quality, and quantity are exceedingly important in a holistic perspective of the annual cycle of caribou forage (Walsh et al 1997, Sturm et al 2005, Gustine et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies involving passive OTC simulate season-long warming rather than advanced growing season and demonstrate small changes in ER, GPP, and NEE (Boelman et al, 2003;Cahoon et al, 2012;La Puma, Philippi, & Oberbauer, 2007;Leffler et al, 2016;Sharp, Sullivan, Steltzer, Csank, & Welker, 2013;Welker, Brown, & Fahnestock, 1999;Welker, Fahnestock, Henry, & O'dea, K. W., & Chimner, R. A., 2004) and increased plant biomass in Arctic systems (Doiron, Gauthier, & Lévesque, 2014;Hollister, Webber, & Bay, 2005;Wookey et al, 1995). At the same site, a concurrent study suggested seasonlong warming can increase abundance of Salix ovalifolia in the system (Carlson, Beard, & Adler, 2018). The nonsignificant season advancement effect on GPP/NEE (Figure 4) suggests that any increase in stem elongation in the season advancement plots (Figure 1) Supporting Information Tables S1-S5 Our experimental manipulation produced CO 2 exchange values similar to those observed in unmanipulated grazing lawns.…”
mentioning
confidence: 99%